Assembly processes of rhizosphere and phyllosphere bacterial communities in constructed wetlands created via transformation of rice paddies - Deng, Nan; Liu, Caixia; Tian, Yuxin; Song, Qingan; Niu, Yandong; Ma, Fengfeng (Frontiers in Microbiology, 2024)
Constructed wetlands are an efficient and cost-effective method of restoring degraded wetlands, in which the microorganisms present make a significant contribution to the ecosystem. In this study, we comprehensively investigated the patterns of diversity and assembly processes of 7 types of constructed wetlands at the rhizosphere and phyllosphere levels. The results showed that the rhizosphere communities of the constructed wetlands exhibited a more balanced structure than that of paddy fields, and 5 types of constructed wetland demonstrated higher potential diversity than that of paddy fields. However, the opposite trend was observed for the phyllosphere communities. Analysis of mean nearest taxon difference indicated that both deterministic and stochastic processes affected the establishment of the rhizosphere and phyllosphere communities, and stochastic processes may have had a larger effect. An iCAMP model showed that dispersal limitation was the most important factor (67% relative contribution) in the rhizosphere community, while drift was the most important (47% relative contribution) in the phyllosphere community. Mantel tests suggested that sucrase, average height, top height, total biomass, belowground biomass, maximum water-holding capacity, and capillary porosity were significantly correlated with processes in the rhizosphere community, whereas factors such as the deterministic process, average height, top height, and SOC were significantly correlated with deterministic processes in the phyllosphere community. Our results can assist in the evaluation of artificial restorations, and can provide understanding of the ecological processes of microbial communities, as well as new insights into the manipulation of microorganisms in polluted wetland ecosystems.